The effects of menisectomy: A follow-up study of the effects of menisectomy on lower limb muscle strength, and on knee joint function - Joanne Enslin (AOSIS, 1983)
The object of this study was to determine the long term results of uncomplicated menisectomies in 16 patients who were at least 8 months post-operative. The average age of the patients was 25 years and all had right dominant legs. Seven of the subjects had undergone right knee surgery, and the remaining eight left knee surgery. Questionnaires were answered to determine the patients' current symptoms and functional ability. Fifteen patients attended a physical examination to assess quadriceps and hamstring muscle strength. The findings were compared to a control group of subjects who had not undergone knee surgery. This study shows that: (i) Sixty percent of the patients had some symptoms such as stiffness, swelling, pain or discomfort, locking, weakness and instability. Seventy-five percent of the patients had some functional limitations during for example squatting, kneeling, climbing stairs, walking on rough ground etc, and half of these surgical patients had some pain and discomfort, as well as difficulty in squatting and kneeling. (ii) Eight months after surgery, the patients had still not regained full muscle strength despite having undergone normal rehabilitation procedures. Isokinetic muscle testing showed a decrease in quadriceps muscle strength in the right-operated leg, the left-operated leg and the right unoperated leg. There was also an increase in right hamstring muscle strength in the right-operated leg. These findings suggest that even uncomplicated menisectomy is not a trivial procedure and that current practices in muscle rehabilitation following menisectomy are not adequate. There should be routine procedures whereby all patients can receive appropriate and adequate muscle rehabilitation after knee surgery.